VOA Video Materials for Listening Class: An Attempt in Engaging Students' Listening Skills - Anita Fatimatul Laeli (Research And Innovation In Language Learning (RILL), 2021)
This case study is aimed to describe the implementation of VOA learning English materials for listening class. Twenty-one participants involved in this study were selected based on the teacher's recommendation and the level of English proficiency, especially in listening. The data were collected using a listening test, fieldnote, and questionnaire. Based on the analysis, it revealed that students' listening scores do not reach the criterion standard of the school; it still categorized low. However, the implementation of VOA engages the students to actively participate in listening activities. They also highly motivated to learn English and to have more practice in listening comprehension. Further, the students give positive responses to the use of video taken from the VOA Learning English program to improve their listening skills. As a consequence, the teacher needs to upgrade their ability to use technology and able to select appropriate materials for the students.